Kombinasi High Intensity Interval Training (HIIT) dan Resistance Training terhadap Performa Atlet Dayung - Salma Putri Bakti; Dede Rohmat Nurjaya; Ridha Mustaqim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Rowing requires cardiovascular endurance, muscle strength, technical efficiency, and consistent performance throughout the 2000-meter run. Unfortunately, training programs are still dominated by land-based training, which does not accurately reflect the specific conditions and demands of rowing in water. The combination of High-Intensity Interval Training (HIIT) and Resistance Training (RT) has been shown to improve physiological capacity; however, its direct application in water is rarely studied. This study aims to analyze the effect of the combination of HIIT and RT performed in water on improving the performance of rowing athletes. The method used in this study is a quantitative descriptive approach with a One-Group Pretest-Posttest design involving active rowing athletes in Bandung City. The research instrument was a 2000-meter on-water rowing test. The results showed a significant increase in 2000-meter rowing performance after participants received a combination of HIIT and RT training compared to before receiving the training. The combination of HIIT and RT in water has proven to be an effective and applicable training model for improving the performance of rowing athletes. Therefore, we recommend that trainers integrate both HIIT and RT training methods into their performance coaching programs. Keyword : High Intensity Interval Training, Performance, Resistance Training, Rowing Athlete.